Study of Oxidant Ionic Liquid with the Help of Soluble Support - HEIDARIZADEH, FARIBA; ALLAHVERDI, GHADER (Asian Journal of Chemistry, 2010)
A new strategy using a soluble support for oxidation has been developed. The efficiency of this new system has been demonstrated by the use of starch as the support in oxidation of benzylic alcohols to the corresponding aldehydes. Due to the use of soluble support, oxidation reaction has been easier and no overoxidation to carboxylic acids or esters formation was detected. The purification time of the crude product has been considerably shortened.